Higher BMP Expression in Tendon Stem/Progenitor Cells Contributes to the Increased Heterotopic Ossification in Achilles Tendon With Aging - Dai, Guangchun; Li, Yingjuan; Liu, Junyan; Zhang, Cheng; Chen, Minhao; Lu, Panpan; Rui, Yunfeng (Frontiers in Cell and Developmental Biology, 2020)
Although the mineralization in tendon tissue has been reported in a series of aging and disease models, the underlying mechanisms remain unknown. This study aimed to describe the appearance of heterotopic ossification in rat Achilles tendon and further verify whether this tissue metaplasia is related to the enhanced osteogenic differentiation of tendon stem/progenitor cells (TSPCs) owing to the higher expression of bone morphogenetic proteins (BMP-2/4/7) with aging. The male SD rats, aged 4, 8 and 20 month (M), were used. The analyses of ossification and BMPs expression in tendon were tested by radiological view (X-ray and CT), histological staining (Hematoxylin and Eosin (HE), Alcian blue and Alizarin red), immunohistochemistry and Western blot. The osteogenic differentiation potential and BMPs expression of TSPCs were examined by Alizarin red S staining and real-time PCR. TSPCs were treated with BMP-2 or noggin, and the osteogenic differentiation potential were also examined. X-ray and CT showed the appearance of heterotopic ossification in tendon, and the volume and density of ossification was increased with aging. Histological staining showed the appearance of calcified region surrounded by chondrocyte-like cells and the increased osteogenesis-related genes and BMPs expression in ossified tendon with aging. Moreover, the osteogenic differentiation potential and BMPs expression in TSPCs isolated from ossified tendon were increased with aging. Additionally, BMP-2 increased the calcium nodule formation and osteogenesis-related genes expression in TSPCs. The addition of noggin inhibited BMP-induced enhancement of osteogenic differentiation. Thus, these findings suggested that the enhanced osteogenic differentiation of TSPCs contributes to the increased heterotopic ossification in aged tendon, which might be induced by the higher expression of BMPs with aging.